Identification of Bioactive Natural Product from the Stems and Stem Barks of Cornus walteri: Benzyl Salicylate Shows Potential Anti-Inflammatory Activity in Lipopolysaccharide-Stimulated RAW 264.7 Macrophages - Dahae Lee; Akida Alishir; Tae Su Jang; Ki Hyun Kim (MDPI AG, 2021)
Cornus walteri (Cornaceae), known as Walter's dogwood, has been used to treat dermatologic inflammation and diarrheal disease in traditional oriental medicine. As part of an ongoing research project to discover natural products with biological activities, the anti-inflammatory potential of compounds from C. walteri in lipopolysaccharide (LPS)-stimulated mouse RAW 264.7 macrophages were explored. Phytochemical analysis of the methanol extract of the stem and stem bark of C. walteri led to the isolation of 15 chemical constituents. These compounds were evaluated for their inhibitory effects on the production of the proinflammatory mediator nitric oxide (NO) in LPS-stimulated macrophages, as measured by NO assays. The molecular mechanisms underlying the anti-inflammatory activity were investigated using western blotting. Our results demonstrated that among 15 chemical constituents, lupeol and benzyl salicylate inhibited NO production in LPS-activated RAW 264.7 macrophages. Benzyl salicylate was more efficient than NG-monomethyl-L-arginine mono-acetate salt (L-NMMA) in terms of its inhibitory effect. In addition, the mechanism of action of benzyl salicylate consisted of the inhibition of phosphorylation of IκB kinase alpha (IKKα), IκB kinase beta (IKKβ), inhibitor of kappa B alpha (IκBα), and nuclear factor kappa B (NF-κB) in LPS-stimulated macrophages. Furthermore, benzyl salicylate inhibited the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Taken together, these results suggest that benzyl salicylate present in the stem and stem bark of C. walteri has potential anti-inflammatory activity, supporting the potential application of this compound in the treatment of inflammatory diseases.